Perancangan Dashboard Sistem Informasi Pemeringkatan Kinerja Dosen menggunakan Metode Human Centered Design (Studi Kasus: Universitas Brawijaya Annual Quality Award) - Amalia Dwi Indra Ramadhani; Herman Tolle; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
UBAQA is a work program as a form of appreciation from the University for faculties, study programs and work units whose performance has implemented minimum service standards well. But at this time UBAQA only assesses ratings for faculties, study programs and work units, without assessing and ranking lecturers personal performance. So as the management of Brawijaya University and UBAQA organizer needs an assessment and ranking of the lecturers personal performance. From the results of the ranking, the lecturer can be given an appreciation for completing the task well and having work performance. So as to facilitate the implementation of rating, assessment, and Monitoring performance of lecturers personally. UBAQA needs a website-based information system to get information visualizations well. A usable media visualization is a dashboard. To be able to produce an easy dashboard and the user is satisfied, the User Experience (UX) design is done by applying the human centered project method as the project phase of UX and the element of user experience method as a stage in making the project. The stages of this research include the context of usage context, needs analysis, solution design and evaluation. The evaluation in this study uses usability testing on aspects of learnability, efficiency and satisfaction using the System Usability Scale (SUS) questionnaire. Based on the test results found three problems and two respondent feedback related to the project of the solution being tested, so that in the next stage improvements were made to the project of the solution.